Faroe Islands. - Proctor, James, ....- (Chalfont St Peter : Bradt Travel Guides, 2008)
The Faroes are eighteen North Atlantic islands located northwest of Scotland and halfway between Iceland and Norway. Since 1948 they have been an autonomous region of Denmark with their own parliament, flag and official national language. Known for their towering cliffs and mountainous terrain, these islands offer a unique opportunity to hike through some of Europe's most unspoilt landscapes, explore traditional fjordside villages, cycle around remote valleys or watch the 300 or so species of birds. Despite their remote location, the Faroe Islands are easily accessible by sea and air. Luxury ferry service operates from Scotland and Europe, and there are direct flights from Stansted, Aberdeen, and Copenhagen.
Keywords: Faeröer -- Reisgidsen